TR16 Simulation on the move, explored through a realist lens. (November 2018) - Somerville, Susan; Baker, Andrea; McAleer, Sean; Howden, Stella; Schofield, Susie; Ker, Jean
Abstract : Introduction: Enabling access to simulation based education for health care practitioners, irrespective of their professional background, workplace context or geographic setting is challenging and complex. Within a backdrop of a national strategy for clinical skills and simulation based education in Scotland, 1 this research uses a Realist lens as a means to explore the questions; what has worked, for whom, how and why?, in respect of a mobile simulation unit in operation since 2009. Methods: Realist inquiry offers a theory driven approach to the evaluation of complex interventions, programs, services or policies and is used increasingly in health and social care research. 2 Documentary analysis, fieldtrips, and semi-structured interviews have enabled data to be gathered from a range of perspectives, stakeholders and participants, and has offered a way to illuminate, analyse and explore complexity in relation to the mobile simulation concept. Results: This mobile simulation unit has achieved longevity in comparison to similar UK based exemplars. An analysis of retrospective data collected since its launch confirms that in line with proposed outcomes, the mobile simulation unit has achieved broad reach throughout geographic areas, particularly in remote and rural locations. The education delivered has focused on high risk, low frequency events, consistent with a training needs analysis. Simulation use is primarily by medical, nursing and paramedic staff proportionate to the makeup of the NHS workforce. However the heterogeneity of contexts and the causal mechanisms influencing outcomes are multifarious and impact upon capacity and sustainability. Discussion and Conclusion: Realistic Evaluation 3 is deepening our understanding of the issues which support or impede this simulation intervention and this includes the impact of infrastructure, organisation, interpersonal and/or individual factors. This in-depth interpretation is essential to the review and enhancement of mobile simulation. It provides new knowledge that is of value not only for Scotland and its workforce, but also internationally, where there is limited rigorous research in this field. References: Ker J, Cachia P, Beasant B. A national approach for the use of simulation to educate and train the NHS workforce: The first national clinical skills strategy. Scottish Medical Journal2015;60(4):220–2. Greenhalgh T, Wong G, Jagosh J, et al. Protocol—the RAMESES II study: Developing guidance and reporting standards for realist evaluation. BMJ Open2015;5(8):e008567. Pawson R, Tilley N. Realistic evaluation 1997. London: SAGE.